Early French and German central bank charters and regulations - Ulrich Bindseil (European Central Bank (ECB), 2019)
In some recent studies, the question of the origins of central banking has been revisited, suggesting that beyond Swedish and British central banking, a number of earlier European continental institutions would also have played an important role. However, it has often been difficult to access the charters and regulations of these early central banks - in particular in English. This paper contributes to closing this gap by introducing and providing translations of some charters and regulations of six pre 1800 central banks in France and Germany. The six early public banks displayed varying levels of success and duration, and qualify to a different degree as central banks. An overview table maps the articles of the early central banks' charters and regulations into key central banking topics. The texts also provide evidence of the role of central banking legislation, and of the distinction between, on the one side, the statutes and charters of the banks, and on the other side the operational aspects which tend to be framed by separate rules and regulations. Finally, the texts provide evidence of the policy objectives of early central banks, including in particular those of a monetary nature. To put these documents into context, the objectives, balance sheet structure, achievements and closure of each central bank are briefly summarised.
Keywords: E32; E5; N23; 330; origins of central banking; central bank mandates; central bank regulations; central bank operations; central bank governance